Perceptions and Attitudes of Biology Teacher’s Candidate Towards the Potential of Tiktok as a Means of Edutainment in Learning Biology - Nadifah, Ainun; Widi, Dela Renita; Intanti, Fitri Aini Findha; Marta, Nilna Salsabila (Aspirasi Masyarakat Intelektual Islam Nusantara, 2023)
TikTok is a platform for short video destinations from China, which was launched in early September 2016. TikTok applications not only provide entertaining short video and content but also TikTok contents can be used in education. Tiktok shows a very large potential in providing information. The purpose of this research was to learn the perception of biology teacher's candidate for the use of TikTok as potential edutainment in the learning and attitudes of biology teacher's candidate for the used of TikTok in the learning biology. The method in this research was qualitative and quantitative (mix method). The samples used was students in FTIK UIN KHAS Jember Study Program Biology Education for the 2020-2021 academic year even semester 2022/2023, which was 30 students. The instrument used was form of a questionnaire distributed using google form containing 14 questions. The result showed that respondent’s response that the perception of biology teacher's candidate for the used of TikTok as as a Biology learning medium was 74.26%, the response to the used of TikTok as potential edutainment in the biology learning was 72.16% and the teacher's attitude to the used of TikTok in Biology learning was 62.66%. And the used of TikTok was also potential to increase motivation, interaction and creativity in biology learning.